ISO 21001:2018 IN ACADEMIA: A REVIEW OF LITERATURE - Marina Abu Bakar; Sukriah Ismail; Lizawati Mohamad Darwi, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
ISO 21001:2018 is an international standard developed by the International Organization for Standardization (ISO) specifically for educational organizations. It provides a management system framework designed to help educational institutions enhance their ability to deliver quality education and meet the needs and expectations of learners and other beneficiaries. While existing literature on ISO standards in education has primarily focused on information security and quality assurance frameworks, there is a gap regarding the benefits, challenges, and readiness factors associated with adopting ISO 21001:2018 in academia. Therefore, this study aims to analyse these aspects within higher education.This study employs a qualitative research design, comprising secondary data analysed using thematic analysis. The findings reveal that implementing ISO 21001:2018 brings significant benefits like improved efficiency, better educational quality, and higher stakeholder satisfaction. However, challenges such as resource constraints, resistance to change, and ongoing capacity building can hinder its success. Key factors for successful adoption include strong leadership, positive organizational culture, skilled staff, and sufficient resources. The findings imply that educational institutions should align their goals with ISO 21001:2018, address resource challenges, strengthen leadership, invest in staff development, and involve stakeholders in implementation. Continued research and case studies are needed to understand its long-term impact and refine its application.